"Paisagem, desdobramentos e perspectivas contemporâneas", Maria Amélia Bulhões and Maria Lúcia Bastos Kern, editors - Vargas, Antonio (PORTO ARTE: Revista de Artes Visuais, 2013)
"Paisagem, desdobramentos e perspectivas contemporâneas" (or "Scenery, unfoldings and contemporary perspectives", Editora da UFRGS, 2010, pp.303), by many researchers, organized by Maria Amélia Bulhões and Maria Lúcia Bastos Kern, offers us a set of reflexions on the relations between historical concepts of scenery and artistic productions.